Сопространственность, геокультуры и (не)локальные тексты: к транссемиотике провинциальных текстов (ENTHYMEMA, 2022)
The semiotics of provincial texts is the content core of provincial research, ensuring their cognitive growth. Comparative semiotic analysis of provincial texts is faced with the impossibility of direct correlation of the compared texts due to their various phenomenological features. The processes of localization of provincial texts and the procedures for their semiotic identification are also directly related to the concepts of geo-culture and geo-culturality. Any local text assumes the presence or absence of a trans-semiotic ‘shifter’ that connects or disables the text itself to a particular provincial register. The provinciality of the text is formed as a situational mental distancing from both the particular signs of the geo-culture of the represented territory and the signs of its immediate locality. Provincial texts create mutually generating and reproducing spatial ontologies, which can be defined as co-spatialities. The constantly reproducing processes of ‘provincialization’ of texts in the course of increasing their co-spatialities are the ontological basis and subject of trans-semiotics of provincial texts. In ontological terms, provincial texts are spaces of many newly formed divergent meta-symbolic assemblages. The aim of trans-semiotic studies of provincial texts is to study the specifics of transformations and transfigurations of newly emerging meta-symbolic provincial assemblages.